2016
DOI: 10.1155/2016/7032830
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Carbon Fiber Reinforced PEEK Hinge Mechanism Articulation Components in a Rotating Hinge Knee Design: A Comparison of In Vitro and Retrieval Findings

Abstract: Carbon fiber reinforced poly-ether-ether-ketone (CFR-PEEK) represents a promising alternative material for bushings in total knee replacements, after early clinical failures of polyethylene in this application. The objective of the present study was to evaluate the damage modes and the extent of damage observed on CFR-PEEK hinge mechanism articulation components after in vivo service in a rotating hinge knee (RHK) system and to compare the results with corresponding components subjected to in vitro wear tests.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The intraoperative findings of black debris in the tissue, from degraded carbon fiber of the CFR-PEEK implant bearing system, have also been reported in previous literature [16]. The CFR-PEEK design is included in Figure 11 for reference [27]. The carbon fiber debris of the implant has been found to lead to the component loosening and inflammation, correlating to the issues with joint function and pain/swelling experienced by the patients [1,16].…”
Section: Discussionsupporting
confidence: 54%
“…The intraoperative findings of black debris in the tissue, from degraded carbon fiber of the CFR-PEEK implant bearing system, have also been reported in previous literature [16]. The CFR-PEEK design is included in Figure 11 for reference [27]. The carbon fiber debris of the implant has been found to lead to the component loosening and inflammation, correlating to the issues with joint function and pain/swelling experienced by the patients [1,16].…”
Section: Discussionsupporting
confidence: 54%
“…PE inserts are available in 10 to 24 mm thickness. The axes are embedded in bushings and flanges made of CRF-PEEK, a novel biomaterial introduced as bearing articulation in knee arthroplasty for the first time aiming to minimize wear [ 22 , 23 ]. The prosthesis is designed for a ROM from 3° of hyperextension to 140° of flexion and allows a rotation of ±12°.…”
Section: Methodsmentioning
confidence: 99%
“…In an in vitro wear study, the ZrN multilayer coating was able to reduce the amount of CFR-PEEK wear particles produced from the flanges and flexion axis in comparison to the uncoated CoCrMo version of the implant by more than 90% [53]. A study on retrievals with an in vivo service between 12 and 60 months has confirmed the wear patterns on the CFR-PEEK components seen during the in vitro wear simulation test [69].…”
Section: Wear Against Cfr-peekmentioning
confidence: 56%